2014
DOI: 10.1177/0883073814565457
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Epileptiform Discharges in Healthy Infants

Abstract: Most studies on epileptiform discharges in young children were performed using analog electroencephalographic (EEG) recording systems and a limited numbers of electrodes that might have a lower detection rate for epileptiform discharges than modern digital recording systems. Knowing the prevalence of epileptiform discharges in healthy children is critical for a valid interpretation of findings in patients with a suspected epileptic disorder. We reviewed EEG recordings of 393 otherwise healthy children aged 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Previous studies also demonstrated epileptiform activity in EEG of normal children. [4][5][6][7][8]17 We reported a significantly higher prevalence of ED in children aged 6 to 12 years (3.59%) compared with children aged 13 to 18 years (1.2%) and children aged 1 to 5 years (0.45%). This is in agreement with the results obtained by previous studies.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Previous studies also demonstrated epileptiform activity in EEG of normal children. [4][5][6][7][8]17 We reported a significantly higher prevalence of ED in children aged 6 to 12 years (3.59%) compared with children aged 13 to 18 years (1.2%) and children aged 1 to 5 years (0.45%). This is in agreement with the results obtained by previous studies.…”
Section: Discussionmentioning
confidence: 73%
“…This is in agreement with the results obtained by previous studies. 5,7,8 Eeg-Olofsson et al 5 reported a higher prevalence of paroxysmal activity among children aged 6 to 13 years (3.3%) compared with the younger group aged 1 to 5 years (1.18%). Borusiak et al 7 reported a higher prevalence of ED among children aged 6 to 9 years (7.5%) as compared with the older group aged 10 to 13 years (4.9%), without a statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Лишь у 5,3-8,0 % детей, у которых была обна-ружена эпилептиформная активность на ЭЭГ, в даль-нейшем развились эпилептические приступы [18,32]. В одном из последних исследований ЭЭГ у 393 здоро-вых детей в возрасте 12-60 мес было показано, что рас-пространенность эпилептиформной активности у детей в возрасте до 5 лет составила 0,76 %, что значительно ниже, чем у детей старшего возраста [23].…”
unclassified